2010
DOI: 10.3357/asem.2769.2010
|View full text |Cite
|
Sign up to set email alerts
|

My Car Is Sinking: Automobile Submersion, Lessons in Vehicle Escape

Abstract: A vehicle is most easily exited during the initial Floating Phase. We suggest the following escape procedure: SEATBELT(s) unfastened; WINDOWS open; CHILDREN released from restraints and brought close to an adult; and OUT, children should exit first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…For example, when the body core temperature is raised because of sport fatigue or heat strokes up to the extreme measured cases of more than 42 • C (hyperthermia) [8], serious dysfunctions in brain and heart do occur (in some cases, this could be a possible cause for sudden death in sports). On the other hand, when body temperature is lowered to 26 • C or less (hypothermia) because of surgery or therapeutical procedures [9] or for unfortunate events as shipwrecks or avalanches [10][11][12][13], death for fibrillation as well as brain damages are well known to occur [14].…”
mentioning
confidence: 99%
“…For example, when the body core temperature is raised because of sport fatigue or heat strokes up to the extreme measured cases of more than 42 • C (hyperthermia) [8], serious dysfunctions in brain and heart do occur (in some cases, this could be a possible cause for sudden death in sports). On the other hand, when body temperature is lowered to 26 • C or less (hypothermia) because of surgery or therapeutical procedures [9] or for unfortunate events as shipwrecks or avalanches [10][11][12][13], death for fibrillation as well as brain damages are well known to occur [14].…”
mentioning
confidence: 99%
“…Initially, the cold shock response seems to predominate as breath hold ability decreases with water temperature. Hayward et al ( 14 ) demonstrated that at 0°C, it is unlikely that many occupants could hold their breath for the 30 s (including time to lower the simulator) required to exit the simulator and reach the surface; this length of time could occur in a lighter vehicle as water would have to fi ll the cabin before doors or windows could be opened ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…As part of Operation ALIVE (Automobile submersion: Lessons In Vehicle Escape), actual vehicle submersions with subjects in them provided many insights into human escape strategies and limitations ( 10 ). Subsequently, a submersible vehicle simulator was designed to allow multiple immersions in the more controlled settings of a water tank ( 19 ) or swimming pool.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, 5-11% of all drownings occur in submerged vehicles (Giesbrecht & McDonald, 2011). Giesbrecht and McDonald (2010) further identified the phases of the submersion of a passenger car as a) floating, b) sinking and c) submerged. The floating phase was approximately one minute in a reasonably air-tight vehicle.…”
Section: Underwater Competenciesmentioning
confidence: 99%